Improving The Mathematical Problem Solving Ability And Mathematical Disposition Using a Problem Posing Approach - Yusniawati, Yayu; Hendriana, Heris; Maya, Rippi (MEJ (Mathematics Education Journal), 2018)
This research is a quasi experimental research, which aims to examine theachievement and improvement of problem solving skills and mathematicaldisposition of MA students by using Problem Posing approach. The populationin this study is the students of class XI in one MA in Tasikmalaya City. Withthe sample subject is class XI IIS 1 as the control class and XI IIS 3 as theexperimental class which totals the total of 62 students. Data obtained fromresearch instruments in the form of tests (pretest and postes problem solvingability) and nontes (scale of mathematical disposition). After the observation,the data is reviewed and analyzed. Based on the results of research and dataprocessing, obtained: (a) Improvement and achievement of mathematicalproblem solving ability of MA students whose learning using Problem Posingapproach is better than the learning using ordinary learning, and (b)Mathematical disposition of MA students whose learning using ProblemPosing approach better than learning using ordinary learning.